Performance of hollow composite members subjected to cyclic eccentric loading. - Hsu, H.L (Earthquake engineering & structural dynamics.)
This study focused on the experimental examination of how hollow composite members perform when subjected to eccentric lateral loading that induces combined bending and torsional stresses. It was found that premature cracking degraded section integrity and interfered with steel concrete interaction when members were subjected to combined bending and torsion. It was also found that members' bending capacities and ductilities were significantly reduced when the members were subjected to torsion. Relationships among member performance, magnitude of torsion, and sectional aspect ratios were studied to evaluate the torsional effects on member performances and to establish design references for hollow composite member constructions.